Digital Transformation of MSMEs through B2C E-Commerce Adoption: A Study of Mitra Karsa Selaras Cooperative - Chairunnisa, Nurlaila Maysaroh; Qintharah, Yuha Nadhirah; Mahmudah, Hadi; Jalil, Abdul Rasyid (Pena Dimas: Jurnal Pengabdian Masyarakat, 2025)
The rapid growth of information technology has transformed business practices by simplifying complex processes, reducing costs, and expanding market reach through digital platforms such as e-commerce. E-commerce gives many micro, small, and medium-sized businesses (MSMEs) the chance to increase their competitiveness, diversify their product offerings, and carry out quick, inexpensive transactions. However, the low level of digital literacy among its members—the majority of whom are retired women—presents serious difficulties for Koperasi Mitra Karsa Selaras, which oversees 52 MSMEs in Pekayon, Bekasi. Especially during the COVID-19 pandemic, this restriction has made it more difficult for them to adopt technology, which has led to a decline in their income and limited access to markets. By using a business-to-consumer (B2C) e-commerce model as a tactic to increase the digital capability and revenue of cooperatively assisted MSMEs, this community service program sought to address these issues. To guarantee that the activities were founded on already-existing community assets and to encourage the cooperative members' active participation, the program combined the strategies of Asset-Based Community Development (ABCD) and Participatory Action Research (PAR). The three primary activities of the implementation method's community education model were: (1) education to explain the idea and advantages of e-commerce; (2) training to impart technical skills in account creation, product uploading, and transaction management; and (3) mentoring to guarantee that participants could use e-commerce platforms on their own. The findings demonstrated that participants successfully created e-commerce store accounts, improved their comprehension of e-commerce concepts and advantages, and produced digital product catalogues that were prepared for online promotion. Overall, the program contributes to the achievement of several Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure), by empowering women-led MSMEs through digital transformation and inclusive economic participation.